Variation in Riverine Inputs Affect Dissolved Organic Matter Characteristics throughout the Estuarine Gradient - Asmala, Eero; Kaartokallio, Hermanni; Carstensen, Jacob; Thomas, David N. (Frontiers in Marine Science, 2016)
Terrestrial dissolved organic matter (DOM) undergoes significant changes during the estuarine transport from river mouths to the open sea. These include transformations and degradation by biological and chemical processes, but also the production of fresh organic matter. Since many of these processes occur simultaneously, properties of the DOM pool represent the net changes during the passage along the hydrological path. We examined changes in multiple DOM characteristics across three Finnish estuarine gradients during spring, summer and autumn: Dissolved organic carbon (DOC) concentration, coloured DOM absorbance and fluorescence, stable carbon isotope signal of DOC and molecular size distribution. Changes in these DOM characteristics with salinity were analysed in relation to residence time (i.e. freshwater transit time), since increased residence time is likely to enhance DOM degradation while stimulating autochthonous DOM production at the same time. Our results show that the investigated DOM characteristics are highly correlated, indicating common physico-chemical transformations along the salinity continuum. Residence time did not explain variations in the DOM characteristics any better than salinity. Due to large variations in DOM characteristics at the river end-member, conservative mixing models do not seem to be able to accurately describe the occurrence and extent of deviations in DOM properties in the estuaries we investigated.